CAMPFIRE Project in Mbazhe Community, Nkayi District, Zimbabwe: A Conflict of Interests - Zikhali, Whitehead (Advances in Social Sciences Research Journal, 2021)
The introduction of CAMPFIRE projects by the Zimbabwean government in the 1980s-1990s was received with mixed feelings especially in Matabeleland provinces as many people were displaced in preference for wildlife. The government viewed CAMPFIRE projects as an antidote to the colonial legacy of technocratic and authoritarian development which undermined people’s control over their environment and criminalised their use of game. This paper seeks to explore why such a potentially positive project was met with mixed feelings by the Mbazhe community in Nkayi District. The deeper conflict between the Mbazhe community and the government in the implementation of the Mbazhe CAMPFIRE project needs careful examination and analysis. The study adopted a qualitative approach as a suitable method of understanding the problem, and complex processes that involved multiple participants in the implementation of this project. Consistent with Lewis Anthony Dexter’s elite interviewing and key informants’ techniques, the study conducted interviews with the 20 villagers and 10 CAMPFIRE project committee members (Dexter 1970). The study concluded that the historical government forces formed the attitudes towards the implementation of the project, by side-lining of local views. The study also revealed that the CAMPFIRE project in the Mbazhe community was further shaped by the legacies of the colonial rule, which was done purely following the authoritarian rule of the white settlers. Consequently, these factors shaped deep suspicion of the CAMPFIRE project and resulted in serious conflicts between the implementers and the affected communities. The study recommended that CAMPFIRE project implementers were/or should consider the inputs of the local people when implementing such projects in their local areas. Also, devolution of power should be promoted among all districts of Zimbabwe so that all districts can benefit from their local resources. Finally, the study recommended that the government should adopt people centred approaches when dealing with people at grassroot level.